Pessimistic Strategy in Negative Politeness Study in Thor: Ragnarok Movie - Listyari, Ni Luh Putu; Aryani, I Gusti Agung Istri; Malini, Ni Luh Nyoman Seri (Humanis; Vol 26 No 1 (2022), 2022)
Good communication is the basis of a good relationship. In achieving the appropriate goals, responses, and reciprocities of speech, people tend to apply the value of decency. The pessimistic strategy of negative politeness is analyzed in this study. The data  used in this study is taken from the Thor: Ragnarok Movie. This study analyzes the type of pessimistic strategy of negative politeness, such as negative, subjunctive, and remote-possibility makers. Besides, this study analyzed the factors that influence the character who used the pessimistic strategy. Factors are relative force, social distance, and level of imposition. The analysis of types and factors is based on the courtesy theory of Brown and Levinson's book "Politeness Some Universals in Language Usage" (1987). The result showed that all of the three types of pessimistic strategy in negative politeness is found in Thor: Ragnarok Movie.  The negative was found in the use of tag questions.  The subjunctive could be found in the use of the would, should,  and the use of the IF  clause. The  remote-possibility makers was found in the use of word hope, supposed, though, and perhaps.  The most type pessimistic strategy found in this data is the use of the subjunctive and the most factor which influences the characters is the size of imposition.